Association of plasma biomarkers of Alzheimer’s pathology and neurodegeneration with gait performance in older adults - Farwa Ali; Jeremy A. Syrjanen; Dan J. Figdore; Walter K. Kremers; Michelle M. Mielke; Clifford R. Jack; David S. Knopman; Prashanthi Vemuri; Jonathan Graff-Radford; B. Gwen Windham; Leland R. Barnard; Ronald C. Petersen; et al. (Communications Medicine)
Abstract Background Declining gait performance is seen in aging individuals, due to neural and systemic factors. Plasma biomarkers provide an accessible way to assess evolving brain changes; non-specific neurodegeneration (NfL, GFAP) or evolving Alzheimer’s disease (Aβ 42/40 ratio, P-Tau181). Methods In a population-based cohort of older adults, we evaluate the hypothesis that plasma biomarkers of neurodegeneration and Alzheimer’s Disease pathology are associated with worse gait performance. A sample of 2641 Mayo Clinic Study of Aging participants with measurements of plasma biomarkers and gait parameters was analyzed in this cross-sectional study. Linear regression models using plasma biomarkers as predictors of gait parameters and adjusted for age, sex, BMI, Charlson Comorbidity Index, and cognitive diagnosis were evaluated. Results In this study multiple statistically significant relationships are observed for GFAP, NfL, and P-Tau181 with gait parameters. Each standard deviation increase in GFAP, NfL, and P-Tau181 is associated with a reduction in velocity of 2.100 (95% CI: −3.004, −1.196; p = 5.4 × 10−6), 4.400 (−5.292, -3.507; p = 9.5 × 10−22), and 2.617 (−3.414, −1.819; p = 1.5 × 10−10) cm/sec, respectively. Overall, NfL has the strongest associations with poor gait performance. Models with age interactions show that the strength of associations between the plasma biomarkers and the gait parameters became stronger with increasing age. There are no specific gait parameters that associate with individual plasma biomarkers. Conclusion Plasma biomarkers of neurodegeneration and Alzheimer’s Disease pathology are not only markers of cognitive decline but also indicate motor decline in the aging population.